DARI PINGITAN KEPELAMINAN; TRADISI YANG MASIH LESTARI DI DESA KRENCENG KECAMATAN KEPUNG KABUPATEN KEDIRI - Muhammad Al Faruq; Annisa Nuril Zahratus Tsania; Moch. Azis Qoharuddin; Achmad Asfi Burhanudin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Marriage is one of the essential aspects of human life, established in accordance with religious law (sharia). However, its implementation is often influenced by the traditions and customs prevailing in the local community. Customs are a key component that reflects the cultural identity of a society. As ancestral heritage, they function not only as a guide for social life but also as a means to strengthen communal bonds. One such tradition that continues to be practiced today is the pingitan tradition in Krenceng Village, Kepung District, Kediri Regency. Based on this context, the researcher raises the following questions: What is the concept of the pingitan custom in the tradition of the Krenceng Village community? What are the challenges and solutions in preserving the pingitan tradition in today’s modern era? And how does Islamic law view the pingitan custom as part of the marriage process prior to the marriage contract (akad nikah)? The objectives of this research are: to explore the concept of pingitan in the local tradition of Krenceng Village; to identify the challenges and solutions in maintaining the pingitan tradition in the modern era; and to examine the Islamic legal perspective on the practice of pingitan prior to the marriage contract. The findings indicate that pingitan, although not regulated by formal customary law, is still practiced by the community as it is considered important for preserving the dignity and purity of the bride-to-be, as well as serving as a period of spiritual and psychological preparation. This tradition now faces challenges from modernization, shifting values, and increasing female participation in the public sphere. As a solution, its implementation is being adapted with an emphasis on educational, spiritual, and symbolic aspects to maintain its relevance. From the perspective of Islamic law, pingitan is not obligatory but may be accepted as ‘urf shahih (valid custom) if it aligns with sharia principles, does not cause undue hardship, and brings benefit (maslahah). This tradition aligns with the objectives of Islamic law (maqāṣid al-sharī‘ah) as long as it is practiced proportionally.